Assessment of potential hazard for humans when eating apples and grapes treated with insecticide based on spiromesifen - I.V. Tkachenko; A.M. Antonenko; V.G. Bardov; S.T. Omelchuk (Medičnì Perspektivi)
Chemical plant protection products account for at least 3 % of all biosphere pollutants and are the most studied pollutants on our planet. A very significant potential risk to public health is the consumption of foodstuffs contaminated with residual quantities of pesticide compounds. The aim of the work was to assess the potential hazard to humans when eating apples and grapes treated with an insecticide based on spiromesifen. A stepwise study was used: the content of spiromesifen in apples and grapes was calculated; the risk to humans was assessed (comparing the values of the permissible daily intake of the compound with food products with the maximum possible daily intake); the integral hazard index of pesticide-contaminated products consumption was calculated and assessed. The results obtained for the determination of residual amounts of spiromesifen in apples and grapes made it possible to substantiate the value of its maximum allowable value – 0.02 mg/kg; apple and grape juices – 0.01 mg/kg. It was found that the actual intake of spiromesifen with apples and grapes can be 0.0065 mg, and this does not exceed 0.5% of the permissible daily intake, or 0.7% of the estimated permissible amount of spiromesifen that can be consumed with food. According to the value of the integral index of hazard in contaminated food consumption (6 points) spiromesifen belongs to class 3 – moderately dangerous to humans. It has been established that substantiated standards for spiromesifen make it possible to ensure the safety of consumption of grapes and apples grown with the Oberon Rapid 240 SC application, as well as the use of other pesticide formulations based on this substance on other crops.